Alignment of Blue/Green and Red Early-type Galaxies with Large-scale Filaments Reveals Distinct Evolutionary Pathways - Yu Rong; Peng Wang (The Astrophysical Journal)
We investigate the alignment of nonred early-type galaxies (ETGs) with blue or green colors within large-scale filaments and compare this alignment pattern with that of red ETGs. Our analysis reveals a significant alignment of the major axes of red ETGs with the orientations of their host cosmic filaments, consistent with prior research. In contrast, nonred ETGs show no significant alignment signal. This divergence in alignment behavior between nonred and red ETGs plausibly suggests distinct evolutionary pathways for nonred and red ETGs.